Anthems and Politics in the Restoration Chapel Royal. Issue 3 (4th October 2021) - White, Bryan
Abstract: This article investigates occasional anthems written for the Chapel Royal by Henry Purcell, John Blow, and William Turner in an attempt to understand the political work enacted through their texts and settings. The anthem's place in the liturgy and its relationship to the sermon is considered, along with the ways in which anthem texts were selected, compiled, and adapted from source texts. Though occasional anthems usually served to interpret current events favourably for the regime, during the crisis caused by James II's prosecution of the Seven Bishops Blow set texts that can be interpreted as challenging the king's pro-Catholic policies. The article concludes by considering the extent to which the characteristics of an anthem text can be used to speculate on the occasion for which it was selected when that occasion is unknown, using the example of Purcell's My song shall be alway .